Efeito do WEB 2170, um antagonista específico do fator ativador de plaquetas (PAF) no trato reprodutivo em ratas - Chaves, Vivianne Calheiros (1990)
Evi dence to support a role for platelet activating factor <PAF) in reproduction was provided through s tud i es wi th the specif íc PAF-receptor antagonist, WEB 2170 during peri-implantation signi fícantl y 1nhibi ted ovaimplantation in rats at a dose range of 1 to 10mg/Rô. i p Pregnancy in these rats was interrupted by 33.3%; 50% and 66.6% -For the respective doses of 1; 5 and lOmg/Kg However', the dose o-f 20mg/Kg did not evidence a further increase in the pregnancy inhi bi tion No difference in the inhibitions of pregnancy was observed whether WEB 2170 treatment was given on days 4 to 6 or on day s 1 to 7 indicating the likely effect of the drug on ni dation process The dose of bmg/Hg WEB 2170 that inhibited pregnancy by 50% was also found to supress more profundly the PAF- i nduced rather than carrageenan or Brewer's yeast-induced edema in the hind paw o-f rats indicating íts specificity to b 1 oc k the PAF-receptor Several other drugs of anti - 1nflammatory nature such as dexametasone (phospho11pase Ae i nhi bi tor >, EP 10161 ( 11poxygenase 1 nhi b i tor) and 1ndomethacin í ciclaxygenase inhibitor) were also found to inhibit pregnancy in Nevertheless. the a manner similar to that of inhibitory potency of WEB 2170 WEB 2170 on ovoimplantation was not enhanced when comb1ned w i th eicosanoid synthesis inhibitors These observations reflected the importance of ínflammatory process in ovoimplantatian and also leave the possibility of PAF mediating its effect through the liberation o-F eicosanoids1. WEB 14, 1 n 2170 administred to a dose of 5mg/kg, i'p pregnant rats on days 8 to affected or ganogenes 1 s and promoted fetal resorpt ions The PAF antagomst under study did not influence the uterotropic action of exogenous estrogen in immature rats It suggests that WEB 2170 possess neither estrogenic nor antiestrogenic property. In regularly 10 consecutive days, reduced the incidence o-F estrus and prolonged the diestrus phase of the reproductive cycle Norma 1 CYdes were, however, restored within 20 days following the cessation of treatment